Analyses of aerodynamic characteristics of the oropharynx applying CBCT: obstructive sleep apnea patients versus control subjects - Chen, Hui; Li, Yingguang; Reiber, Johan HC; de Lange, Jan; Tu, Shengxian; van der Stelt, Paul; Lobbezoo, Frank; Aarab, Ghizlane (Dento-maxillo-facial radiology, 2018)
To determine the most relevant aerodynamic characteristic of the oropharynx related to the collapse of the upper airway in obstructive sleep apnea (OSA) patients; and to determine the correlation between the most relevant aerodynamic characteristic(s) of the oropharynx and anatomical characteristics of the oropharynx in OSA patients. 31 mild to moderate OSA patients (mean ± SD age = 43.5 ± 9.7 years) and 13 control subjects (mean ± SD age = 48.5 ± 16.2 years) were included in this prospective study. The diagnosis of OSA patients was based on an overnight polysomnographic recording. To exclude the presence of OSA in the control subjects, they were asked to fill out a validated questionnaire to determine the risk of OSA. NewTom5G cone beam CT (CBCT) scans were obtained from both OSA patients and control subjects. Computational models of the oropharynx were reconstructed based on CBCT images. The aerodynamic characteristics of the oropharynx were calculated based on these computational models. Pearson correlation analysis was used to analyse the correlation between the most relevant aerodynamic characteristic(s) and anatomical characteristics of the oropharynx in OSA patients. Compared with controls, the airway resistance during expiration (R ) of the OSA patients was significantly higher (p = 0.04). There was a significant negative correlation between R and the minimum cross-sectional area (CSA ) of the oropharynx (r = -0.41, p = 0.02), and between R and the volume of the oropharynx (r = -0.48, p = 0.01) in OSA patients. After excluding an outlier, there is only significant correlation between R and the CSA of the oropharynx (r = -0.45, p = 0.01). Within the limitations of this study, we concluded that the most relevant aerodynamic characteristic of the oropharynx in the collapse of the upper airway in OSA patients is R . Therefore, the repetitive collapse of the upper airway in OSA patients may be explained by a high R , which is related to the CSA of the oropharynx.